2016
DOI: 10.1002/1873-3468.12198
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1‐treated oxLDL promotes cholesterol efflux from macrophages by stimulating the PPARγ–LXRα–ABCA1 pathway

Abstract: Edited by Laszlo NagyHere, we investigate the mechanism through which paraoxonase 1 (PON1) may regulate cholesterol efflux. Pretreatment of oxLDL with PON1 (oxLDL-PON1) contributed to the formation of LysoPC. In J774 macrophages, oxLDL-PON1 increased cholesterol efflux by more than 47% compared to oxLDL alone. oxLDL-PON1 significantly increased mRNA and protein expression of ABCA1 and ABCG1, as well as of PPARc and LXRa compared to oxLDL alone. Intraperitoneal injection of oxLDL-PON1-or LysoPC-treated J774 mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 65 publications
1
27
1
Order By: Relevance
“…that apigenin can influence lipid metabolism by activating PPARγ [51]. As PPARγ/LXRα pathway has been well demonstrated in the regulation of ABCA1 expression [6,52,53], this pathway may also be responsible for apigenin-induced up-regulation of ABCA1 expression and cholesterol efflux, which still warrants further investigation. In addition to lipid disorder, persistent and chronic inflammation within vessel walls also gives a great impetus to AS progression [54].…”
Section: Discussionmentioning
confidence: 90%
“…that apigenin can influence lipid metabolism by activating PPARγ [51]. As PPARγ/LXRα pathway has been well demonstrated in the regulation of ABCA1 expression [6,52,53], this pathway may also be responsible for apigenin-induced up-regulation of ABCA1 expression and cholesterol efflux, which still warrants further investigation. In addition to lipid disorder, persistent and chronic inflammation within vessel walls also gives a great impetus to AS progression [54].…”
Section: Discussionmentioning
confidence: 90%
“…Chawla et al [32] reported that the absence of macrophage PPARγ-LXRα-ABCA1 pathway disrupts cholesterol efflux and aggravates atherogenesis in vivo . Ikhlef et al [64] determined that oxLDL–paraoxonase 1 (PON1) potently amplified cholesterol efflux through the PPARγ-LXRα-ABCA1/G1 pathway in J774 macrophages compared to ox-LDL alone. Besides, salvianolic acid B (Sal B) can also promote the efflux of excess cellular cholesterol from THP-1 cell lines by activating the PPARγ-LXRα-ABCA1 pathway [65].…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine (LysoPC) plays a role in HDL-PON1-induced cholesterol efflux (26). Incubation of oxLDL with PON1 has been shown to liberate LysoPC.…”
Section: Hdl Pon1 and Reverse Cholesterol Transportmentioning
confidence: 99%
“…Incubation of oxLDL with PON1 has been shown to liberate LysoPC. Treatment of J774A.1 macrophages with the oxLDL-PON1 complex increased apoA-I-mediated cholesterol efflux compared to oxLDL in the absence of PON1 (26). Purified LysoPC mimicked effects of oxLDL-PON1 on macrophage cholesterol efflux.…”
Section: Hdl Pon1 and Reverse Cholesterol Transportmentioning
confidence: 99%
See 1 more Smart Citation